THE ACCELERATION RESPONSE SPECTRUM AND EFFECTIVE DURATION OF LEBAK EARTHQUAKE JANUARY 23, 2018 IN JAKARTA REGION - Muhammad Fikri Hayqal Hiola; Bambang Sunardi (Spektra: Jurnal Fisika dan Aplikasinya, 2019)
Jakarta is the capital city of Indonesia with a very high population density low to the upper distribution of buildings which causes many areas of Jakarta to have a high vulnerability to natural disasters, one of which is an earthquake. One of the earthquakes felt this year was Lebak Banten Earthquake January 23, 2018, with a magnitude 6.1 at 13.34 local time. The depth of the earthquake was 61 Km at -7.09o S - 106.03o E, in the South Indian Ocean of Java Island. The epicenter was 43 km from Cilangkahan Village, Malingping Sub-district, Lebak District, Banten. We analyze the ground motion characteristics in the Jakarta area using 3 component acceleration data at Jakarta City Hall Office (JAKO) and Tanjung Priok Maritime Station (JATA) with dynamic statistical analysis method. The effective duration and earthquake response spectrum are determined using the acceleration data. In this study, the active period of the earthquake was calculated using the Trifunac and Brady method. The results of the analysis show that the most significant acceleration spectrum at JAKO station is found in component E of 0.07742 g in the period of 0.54 s while for the most significant acceleration spectrum JATA station found in component N of 0.04572 g in the period of 0.58 s. The effective duration obtained at JAKO stations was 56.76 s and JATA station 63.47 s. These results indicate that in the case of the Lebak earthquake, the further region from the epicenter of the earthquake has an effective duration which is relatively longer.